Feasibility of Engineering Mechanics E-Modules Developed Using the Four-D Model - Erma Yulia; Benyamin Situmorang; Binsar M Pakpahan (Jurnal Penelitian Pendidikan IPA, 2024)
Technological developments demand that learning media be developed on an electronic basis. Availability of electronic modules in Engineering mechanics lessons is currently still not available. Even though students are required to solve cases in the field by mastering three concepts, namely mathematics, physics and mechanics independently. This research aims to determine the feasibility of a case-based engineering mechanics e-module. The research method uses the R&D method with a 4D development model. The stages of the 4D method are definition, design, development and distribution. The data collection technique was carried out by distributing questionnaires. Validation of the e-module was carried out by material experts, learning design experts and learning media experts who were analyzed descriptively. The research results showed that the feasibility score for material experts was 91.17% in the very good category, learning design experts 93.38% in the very good category, and learning media experts 89.83% in the very good category. Thus, it can be concluded that the case-based e-module developed is very suitable for use in learning engineering mechanics.